Nuutsih: interpretation of Celuk village revival via soundscape as a cultural phenomenon - Ni Nyoman Srayamurtikanti; Bambang Sunarto (Pascasarjana Institut Seni Indonesia Surakarta, 2022)
This article discusses the process of creating a work of performing arts entitled